Visualization Technology in High School Chemistry: A Systematic Review on Representations and Pedagogical Strategies - Rahma Tia; Hari Sutrisno (Universitas Negeri Gorontalo, 2026)
The basic concept of chemistry which can’t be seen or touched poses a major cognitive challenge at the secondary school level, making the integration of digital visualization technologies essential for facilitating students' understanding of chemical representations. This study aims to analyze emerging trends in digital visualization technologies and identify the pedagogical strategies most prominently employed to support the development of chemical representational competence. A Systematic Literature Review (SLR) was conducted following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol, analyzing 27 articles retrieved from the Scopus, ERIC, and Springer databases published between 2015 and 2025. The findings indicate that interactive simulations and computer-based visualization tools represent the dominant digital visualization technology trend, primarily supporting an integrated representation pattern that connects the macroscopic, sub-microscopic, and symbolic levels. Analysis of learning strategies revealed six principal categories, with Inquiry & Discovery Learning as the most frequently integrated model (25.9%), followed by Computational & Multimedia Learning (18.5%) and Model-Based Learning (14.8%). These findings suggest that the effectiveness of digital visualization technologies in chemistry education is contingent upon its strategic integration within active pedagogical designs that position students as active participants in constructing conceptual understanding through scientific inquiry.